Implementasi Kegiatan Didikan Subuh dalam Pembentukan Karakter Religius pada Santri Usia Dini - Hamidi, Rera Delvi Elina; Wardefi, Riza (Asian Journal of Early Childhood and Elementary Education, 2024)
Religious character is one of the characters that must be developed in students, because religious character is very much needed by students to face the changing times and moral decline, where students are expected to have standards of right and wrong based on religious rules and are able to act accordingly (Ahsanulkhaq, 2019). This study aims to analyze the implementation of dawn education activities in the formation of religious character in early childhood students at the MDTA Baitus Shafa Talang Babungo Mosque. This study uses a qualitative case study method with informants, namely the head of MDTA, three MDTA teachers and MDTA students from kindergarten, grade I elementary school, and grade II elementary school levels. Data were analyzed through data reduction, data presentation and data conclusions. Data validity techniques use source triangulation and technical triangulation. The results of this study are the planning carried out including forming groups, preparing themes, preparing materials, making event schedules, determining the implementers of dawn education, distributing materials, and rehearsals. Then the stages of implementing activities consist of preliminary activities, core activities and closing activities. Meanwhile, at the eval_uation stage, dawn education activities are held every week and eval_uations are held at the end of each semester.